Improving Leadership Style in Startup to Increasing Team Performance - Khausal, Adam; Dewi, Emilia Fitriana (Proceedings International Conference on Education Innovation and Social Science, 2023)
Startup can be defined as an organization that is either recently created or in the early stages of development and is focused on monetizing a concept. Startups often have a small core team made up of management from the executive, marketing, finance, and operations departments. Teman Survei is a property survey service that can be ordered through our marketplace website more easily and effectively. problem faced by the Teman Survey is a leadership style that is inappropriate and too free for the team to explore more outside the business so that the team becomes out of control and of course there is often a loss of responsibility between teams. Leadership that lacks leadership in this team makes team performance decrease and results in a slow growth company This problem causes the slow growth of the company. The goal of this study is to know how the leadership situation in Teman Survei team and to know how to improve leadership by defining leadership styles and make an implemented plan to increase team performance. This study uses qualitative methods that include Literature review, Data Collection, In-Depth interview, and pragmatism as data analysis and interpretation. The results show that the leadership style carried by the leader is a servant style and an adaptive style which makes the leader lose control of the team. this makes implementation planning in the future will be in the form of implementing a Full-Range leadership style which is a combination of Transformational style and Transactional style.